Pregunta
Solve \( 6=2(13+2 f) \)
Ask by Murray Joseph. in Spain
Feb 03,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( f = -5 \)
Solución
To solve the equation \( 6 = 2(13 + 2f) \) for \( f \), follow these steps:
1. **Expand the Right Side:**
\[
6 = 2 \times 13 + 2 \times 2f
\]
\[
6 = 26 + 4f
\]
2. **Isolate the Term with \( f \):**
Subtract 26 from both sides to move the constant term to the left side.
\[
6 - 26 = 4f
\]
\[
-20 = 4f
\]
3. **Solve for \( f \):**
Divide both sides by 4 to isolate \( f \).
\[
f = \frac{-20}{4}
\]
\[
f = -5
\]
**Final Answer:** \( f = -5 \)
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Extra Insights
To solve the equation \( 6 = 2(13 + 2f) \), first distribute the 2 on the right side: \[ 6 = 2 \cdot 13 + 2 \cdot 2f \] This simplifies to: \[ 6 = 26 + 4f \] Next, isolate the term with \( f \) by subtracting 26 from both sides: \[ 6 - 26 = 4f \] So, \[ -20 = 4f \] Now, divide both sides by 4 to solve for \( f \): \[ f = \frac{-20}{4} = -5 \] Thus, the solution is \( f = -5 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium